Service Quality Pada Bank Perkreditan Rakyat - Kemala Dewi (Guna Sewaka, 2022)
This research to aim for analysis the importance service quality in service company, for the first in BPR. Currently, BPR is experiencing a slump due to the crisis of public confidence in utilizing banking products. This is due to the low quality of services implemented by BPR. This research method uses descriptive qualitative analysis where the research focuses on literature review. The results of this study indicate that service quality has an important role in increasing customer satisfaction, which continues to customer loyalty which is a sustainable advantage for BPR as measured by 5 dimensions of service quality